A reproducible ddRAD-seq protocol reveals novel genomic association signatures for fruit-related traits in peach - Ksouri, Najla; Sanchez, Gerardo; Font i Forcada, Carolina; Contreras-Moreira, Bruno; Gogorcena Aoiz, Yolanda (BMC, 2025)
Improving peach cultivars with superior traits is a primary objective of breeding initiatives. In this study, we aimed to elucidate the genetic basis of key agronomic and fruit-related traits using a reproducible ddRAD-seq protocol applied to a discovery panel of 90 peach accessions. Our customized workflow (available at https://github.com/najlaksouri/GWAS-Workflow) integrates three variant callers and tests up to seven models to perform a robust genome-wide association analysis (GWAS). This approach produced 13,045 high-confidence SNPs and identified Blink as the most suitable model, effectively balancing false positive and negative associations. A total of 16 significant associations signals were unveiled for six highly heritable traits (H2 > 0.5), including harvest date, fruit weight, flesh firmness, contents of flavonoids, anthocyanins and sorbitol. By assessing the allelic effect of significant markers on phenotypic attributes, nine SNP alleles were deemed favorable. Notably, a promising marker (SNC_034014.1_7012470) demonstrated simultaneous association with harvest date and fruit firmness, displaying a positive allelic effect on both traits. We anticipate that this marker can serve as a good predictor of firmer varieties. Candidate causal genes were shortlisted when fulfilling the following criteria: (i) position within the linkage disequilibrium block, (ii) functional annotation and (iii) expression pattern. A comprehensive bibliographic review of previously reported QTLs mapping nearby the associated markers allowed us to benchmark the accuracy of our approach. Despite the moderate germplasm size, ddRAD-seq allowed us to produce an accurate representation of the peach genome, resulting in SNP markers suitable for empirical association studies. Together with candidate genes, they lay the foundation for further genetic dissection of peach key traits.